2014
DOI: 10.1016/j.ecolecon.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Green hypocrisy?: Environmental attitudes and residential space heating expenditure

Abstract: In the UK, the largest proportion of household energy use is for space heating. Popular media make claims of a green hypocrisy: groups which have the strongest attitude towards the environment have the highest emissions. This study examines whether environmental attitudes and behaviours are associated with space heating energy use using data from the British Household Panel Survey. Results find that environmentally friendly attitudes generally do not lead to lower heating expenditures though environmentally fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
(19 reference statements)
6
30
1
Order By: Relevance
“…The divergence of the results between climate change concern and pro-environmental actions on the effect of education also helps ensure against the claims of a green hypocrisy by popular media. Green hypocrisy refers to groups with the strongest environmentally friendly attitudes while at the same time having the highest emissions or being more likely to take actions that are most harmful to the environment (Lange et al, 2014). In contrast, according to our results, those who have spent more years in education although are not shown to have a greater concern towards the environment, they are more likely to express it in terms of actions.…”
Section: Knowledge-based Pro-environmental Actionscontrasting
confidence: 53%
“…The divergence of the results between climate change concern and pro-environmental actions on the effect of education also helps ensure against the claims of a green hypocrisy by popular media. Green hypocrisy refers to groups with the strongest environmentally friendly attitudes while at the same time having the highest emissions or being more likely to take actions that are most harmful to the environment (Lange et al, 2014). In contrast, according to our results, those who have spent more years in education although are not shown to have a greater concern towards the environment, they are more likely to express it in terms of actions.…”
Section: Knowledge-based Pro-environmental Actionscontrasting
confidence: 53%
“…Green and Tunstall (1999) indicate that reports regarding hypothetical situations do not coincide with those in which the situations are real. This statement falls in line with the results reported by Lange et al (2014), who found that environmental attitudes and environmental behaviors yield to 1 This is a certification system for high-energy efficiency products from the U.S. Green Building Council. different results.…”
Section: Datasupporting
confidence: 80%
“…An explanation could be the so-called 'compliance bias' which makes respondents state a socially accepted WTP due to the influence of social norms (Green and Tunstall, 1999). This divergence runs in parallel with the results found by Lange et al (2014) (see section 2).…”
supporting
confidence: 80%
“…Additionally, we include questions related to both environmentally-friendly attitudes and behaviors. Previous findings (Lange et al, 2014) showed that questions related to current behavior are expected to be better indicators of future actions than questions based on attitudes, as indicated by psychologists (Kollmuss and Agyeman, 2002). In the environmental valuation literature it is well-known that social pressure can lead respondents to report socially acceptable answers that might bias the effect of stated preferences (Green and Tunstall, 1999;Kollmuss and Agyeman, 2002).…”
Section: Introductionmentioning
confidence: 99%